Nonsegmental, Diffuse Angioma Serpiginosum with Atypical Facial Lesions - Sumit Sehgal; Tarang Goyal; Shweta Grover; Anupam Varshney; Gaurja Juneja (Clinical Dermatology Review)
Angioma serpiginosum is a rare vascular malformation characterized by multiple, asymptomatic macules that commonly appear on the lower extremities. This case report discusses an adolescent female with diffuse, non-segmental AS exhibiting blaschkoid distribution with contralateral spill. Monthly intralesional bleomycin (2 units/ml) was administered to the cosmetically concerning facial lesions, resulting in noticeable flattening within one month. While the treatment showed partial efficacy in reducing the number and size of lesions, it also highlighted the risk of pigmentary changes. This case highlights the clinical efficacy of intralesional bleomycin as a potential treatment for selected lesions of AS, particularly in settings where laser options are limited.